2020
DOI: 10.1371/journal.pone.0240750
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of myopia in Indian school children: Meta-analysis of last four decades

Abstract: Background India is the second most populated country in the world with 41% of the population (492 million) under 18 years of age. While numerous studies have shown an increasing prevalence of myopia worldwide, there continues to be uncertainty about the magnitude of myopia in Indian school going population. Design Systematic review and meta-analysis. Methods We systematically identified published literature of last four decades from 1980 to March 2020 and assessed them for methodological quality. Data were ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 50 publications
0
21
3
Order By: Relevance
“…These include excessive near work and reduced outdoor activities, less exposure to sunlight, and more digital gadget usage in dim light conditions. [ 4 5 6 7 ] Recent studies show that people with high educational qualifications have longer eyeballs compared to people with a lower education background. [ 8 ]…”
mentioning
confidence: 99%
“…These include excessive near work and reduced outdoor activities, less exposure to sunlight, and more digital gadget usage in dim light conditions. [ 4 5 6 7 ] Recent studies show that people with high educational qualifications have longer eyeballs compared to people with a lower education background. [ 8 ]…”
mentioning
confidence: 99%
“…7 Meta-analysis of the last four decades by Agarwal et al showed 10% prevalence of myopia among Indian school children. 8 Higher prevalence was found by Holden et al and Fan et al as 22.9% and 36.71% respectively which is a contrast to a recent study 12.2%…”
Section: Discussionmentioning
confidence: 61%
“…15 Meta-analysis of the last four decades by Agarwal et al showed 10% prevalence of myopia among Indian school children. 16 Higher prevalence was found by Holden et al and Fan et al as 22.9% and 36.71% respectively which is a contrast to a recent study by Grzybowski et al, where the prevalence of myopia was found to be low under 10% in African and South American children. [17][18][19] In this study, there is a statistically significant association between reading hours (1-2 hours) and myopia among school children.…”
Section: Discussionmentioning
confidence: 67%